Intraventricular conduction defects in patients with st-segment elevation myocardial infarction – the paradox of right bundle branch block. (25th November 2020) - Fernandes, S; Montenegro, F; Cabral, M; Carvalho, R; Santos, L; Ruivo, C; Pernencar, S; Morais, J
Abstract: : Intraventricular conduction defects (IVCD) in patients with acute myocardial infarct (AMI) are predictors of a worse prognosis. When acquired they can be the result of an extensive myocardial damage. Purpose: To assess the impact of IVCD, regardless of being previously known or presumed new, on in-hospital outcomes of patients with AMI with ST segment elevation (STEMI) or undetermined location. Methods: From a series of patients included in the National Registry of Acute Coronary Syndrome between 10/1/2010 and 9/1/2019, were selected patients with STEMI or undetermined AMI, undergoing coronary angiography. Results: 7805 patients were included: 461 (5.9%) presenting left bundle branch block (LBBB), 374 (4.8%) with right bundle branch block (RBBB) and 6970 (89.3%) with no IVCD. Clinical characteristics as well as in-hospital outcomes are described in the table 1. An unexpected worse prognosis in patients with RBBB has motivated a multivariate analysis. RBBB remained an independent predictor of in-hospital mortality (OR 1.91, 95% CI 1.04–3.50, p=0.038), along with female gender (OR 1.73, 95% CI 1.11–2.68, p=0.015), Killip Class>1 (OR 2.26, 95% CI 1.45–3.53, p<0.001), left ventricular ejection fraction <50% (OR 3.93, 95% CI 2.19–7.05, p<0.001) and left anterior descending artery as the culprit lesion (OR 1.85, 95% CI 1.16–2.91, p=0.009). Conclusion: In spite of an apparent better clinical profile, in the current large series of unselected STEMI patients, the presence of RBBB is associated with the worst in-hospital outcome. RBBB doubles the risk of death, being an independent predictor of in-hospital mortality. Funding Acknowledgement: Type of funding source: None